1996
DOI: 10.1002/(sici)1096-9861(19960205)365:2<306::aid-cne8>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Organization of afferent and efferent projections of the nucleus basalis prosencephali in a passerine,Taeniopygia guttata

Abstract: The connections of nucleus basalis (NB) of the rostral forebrain of the zebra finch were investigated electrophysiologically and with anterograde and retrograde tracing methods to determine their functional organization, the sources of their pontine afferents, and the targets of their telencephalic efferents. The nucleus was found to be partitioned into three major components, a rostral lingual part that received a hypoglossal projection via a lateral subnucleus of the principal sensory trigeminal nucleus (PrV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 69 publications
3
98
0
1
Order By: Relevance
“…What would actually be the prediction if we imagine a scenario where the vestibular system, not the trigeminal system, would be the source of the magnetic activation we have observed in PrV and SpV? That would mean (i) that the activation of PrV and SpV observed in the CMF condition would represent a combination of vestibular magnetic input and non-magnetic trigeminal input (mechanical [41,42] or maybe even olfactory [43,44]); (ii) that the activation of PrV and SpV in the ZMF condition would represent only nonmagnetic trigeminal input and (iii) that the activation of PrV and SpV in the CMF-sect. group would represent only vestibular magnetic input ( figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…What would actually be the prediction if we imagine a scenario where the vestibular system, not the trigeminal system, would be the source of the magnetic activation we have observed in PrV and SpV? That would mean (i) that the activation of PrV and SpV observed in the CMF condition would represent a combination of vestibular magnetic input and non-magnetic trigeminal input (mechanical [41,42] or maybe even olfactory [43,44]); (ii) that the activation of PrV and SpV in the ZMF condition would represent only nonmagnetic trigeminal input and (iii) that the activation of PrV and SpV in the CMF-sect. group would represent only vestibular magnetic input ( figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…The Bas is involved in feeding and oral-manipulative behaviors other than vocalization and does not anatomically connect to the vocal control system in songbirds (Wild and Farabaugh, 1996). Because both male and female finches engage in oral movements related to feeding behavior, it is not surprising that FoxP1 levels in the Bas are similar in both sexes.…”
Section: Discussion Sexually Dimorphic Expression Of Foxp1 In Songbirdsmentioning
confidence: 99%
“…Because the structure that has been known as the nucleus basalis also shows a core and shell organization, a similar problem exists for it ( Fig. 7D; Wild and Zeigler, 1980;Wild et al, 1985;Veenman and Gottschaldt, 1986;Dubbeldam and Visser, 1987;Wild and Farabaugh, 1996). The Forum concluded that it would be desirable to develop a uniform and consistent terminology for these three sensory areas in the nidopallium and will make recommendations in a separate publication specifically devoted to this issue, in the special nomenclature issue of Brain, Behavior and Evolution.…”
Section: Rationale For Individual Changes: the Neostriatummentioning
confidence: 99%
“…The structure that has been called nucleus basalis in birds is not located in the subpallium and is not a cholinergic cell group, but rather is a trigeminorecipient pallial sensory cell group (Witkovsky et al, 1973;Wild et al, 1985) and, in some species, also a general somatosensory recipient nucleus (Wild et al, , 2001. It also receives an auditory input from the nucleus of the lateral lemniscus, as well as an input from the vestibular system ( (Arends and Zeigler, 1986;Wild and Farabaugh, 1996;Wild et al, 2001). To prevent confusion with the cholinergic nucleus basalis of mammals, the Forum recommended that the old nucleus basalis of birds be renamed the nucleus basorostralis of the pallium, which describes its position in the telencephalon, with no abbreviation change (Table 4, Figs.…”
Section: Rationale For Individual Changes: the Neostriatummentioning
confidence: 99%
See 1 more Smart Citation